2023
DOI: 10.5267/j.dsl.2022.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making model to predict auto-rejection: An implementation of ARIMA for accurate forecasting of stock price volatility during the Covid-19

Abstract: This study aims to determine an accurate forecasting model, especially an error rate of around 0, and to examine how the automatic rejection system reacts to stock price as a result of the pandemic. The statistical clustering method is used for the dataset in form of daily observations, while the sample covers the period of cases before and after COVID-19 pandemic from 02 January 2019 to 20 June 2020 at the Trinitan Minerals and Metal Company. Furthermore, the data used in the estimation are the opening and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…The coefficients of parameters for each model were estimated using R software, and the equations of the models are shown in Table 5 by substituting the given coefficients into Equation (6). ARIMA(1,1,0) for the pre-COVID-19 phase, ARIMA(1,1,0) for the post-COVID-19 phase, and ARIMA(1,1,0) for the overall time span phase are given in Equation (11) to Equation (13). y t = 0.9195y t−1 + 0.0669y t−2 + ϵ t , (11) y t = 0.9341y t−1 + 0.0659y t−2 + ϵ t , (12) y t = 0.9670y t−1 + 0.0321y t−2 + ϵ t .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coefficients of parameters for each model were estimated using R software, and the equations of the models are shown in Table 5 by substituting the given coefficients into Equation (6). ARIMA(1,1,0) for the pre-COVID-19 phase, ARIMA(1,1,0) for the post-COVID-19 phase, and ARIMA(1,1,0) for the overall time span phase are given in Equation (11) to Equation (13). y t = 0.9195y t−1 + 0.0669y t−2 + ϵ t , (11) y t = 0.9341y t−1 + 0.0659y t−2 + ϵ t , (12) y t = 0.9670y t−1 + 0.0321y t−2 + ϵ t .…”
Section: Resultsmentioning
confidence: 99%
“…In financial applications, several researchers [13,16,5] found that the ARIMA model was able to capture the patterns and trends of each financial price movement and predict its future values during the COVID-19 pandemic. Nonetheless, despite the outstanding results, few studies have examined the performance of the ARIMA model during the pre-and post-COVID-19 phases, owing to the massive impact of the pandemic on the financial market [17].…”
Section: Related Workmentioning
confidence: 99%
“…The well-known traditional statistics time series forecasting methods, such as ARIMA and its variants 17,[21][22][23][24][25][26][27][28][29] are still used a lot because of their efficiency level. Table 1 presents a summary of ARIMA-based approaches for SPF.…”
Section: Arima Approachesmentioning
confidence: 99%
“…Additionally, Suripto (2023) recommend that if stakeholders are satisfied with the SME's financial performance and decision-making, it suggests that the SME's capital forecasting process is effective and well-regarded. Thus, the studies highlight the importance of capital forecasting methods, the accuracy of forecasting, factors affecting capital forecasting, and best practices for capital forecasting in SMEs.…”
Section: Capital Forecastingmentioning
confidence: 99%